Perempuan Tenun di Maluku Merawat Alam Dengan Semangat Spiritualitas Ekofeminis - Eklefina Pattinama (Peneliti.net, 2019)
Weaving and women are a package that is a strength of the family economy based on women's local knowledge passed down from generation to generation. Woven women's work requires accuracy, patience, tenacity as an attitude of spirituality. The source of inspiration for weaving comes from nature encouraging women to weave rama towards nature. The theory used in explaining this reality from the perspective of ecofeminism spirituality theory. The data collected in writing this article is sourced from the assessment of data using a qualitative research approach. Research locations on weaving women in Maluku, Ambon City, generally women from Tanimbar (West Southeast Maluku). This paper explains 3 main things: 1). Woven women are the successors of local wisdom in Maluku, 2) Woven Women have a gifted spirituality challenging the motifs of modern textile weaving. Woven women care for nature with the spirit of ecofeminism spirituality.